A study of experience sharing in community engagement - Khalid @ Khalil, Khaiziliyah; Haron, Haryani; Abdullah, Natrah (2016)
Community engagement is crucial in building positive relationships within the members of a community.Community gardening can be a means of community engagement through providing opportunities for social interaction and greater community cohesions.Community engagement will take place when the community gardeners contribute something which is beneficial and visible to the communities. In creating successful community engagement, there is a need of experience sharing among community gardeners.Community gardening can be a means of providing opportunities for social interaction, greater community cohesion and community engagement.This paper aims to look into the real practices of experience sharing for community engagement in the context of community gardening in Malaysia.A comparative study was conducted by looking into two types of community. The finding shows the experience sharing helps the community to be engaged.In fact, community engaged more with the advancement of information technology.